Functional material modelling and simulation of graphene on its various characteristics - Gao, Ying (2015)
Composite materials are materials derived from two or more constituent materials that exhibit distinctively different physical and chemical properties. They are gaining enormous attention and focus for the past few years, due to its flexible mechanical characteristics and extremely light weight. As an important component of the composite materials study, graphene has been researched for decades, but only after its successful isolation, graphene’s extraordinary mechanical, thermal, electrical and optical properties are being considered for real life applications. In order to unveil the exact characteristics of graphene, with the help of a simulation and modelling software program, the structure of graphene were constructed and computational results were obtained. They were then used to compare with natural phenomenon mentioned in the literature reviews, for the purpose of reference and verification. The possibility for abnormality and casual relations were considered the discussed as well.